Proposals for teaching in Special Education: contributions from the Brazilian academic field (Práxis Educativa, 2024)
This research aimed to systematize the main proposals for teaching in Special Education, within the scope of its academic field in Brazil. The theoretical framework is based on Bourdieu (2004a) and Bourdieu, Chamboredon e Passeron (2007), Hey (2008) and previous research (Casagrande, 2020, 2021; Casagrande; Mainardes, 2021a, 2021b; Mainardes; Casagrande, 2022) on the academic field of Special Education. It is characterized as a study of a qualitative, exploratory nature and a bibliographic research type procedure. As a result, a set of proposals from field agents was found, organized into two categories, named as follows: 1. Broader teaching proposals: accessibility, Multi-layered Support System, School Inclusion Support Professionals; and 2. More specific teaching proposals: Universal Design for Learning, Collaborative Teaching, Curricular Differentiation, Evidence-Based Practices, Individualized Educational Plan, Cooperative Learning, Active Methodologies and Assistive Technology. These proposals make up the so-called innovative inclusive practices currently recommended, and which benefit everyone’s learning and development. Agents in the field of Special Education provide, through their research, several productions that, together, indicate possibilities for achieving school inclusion.Keywords: Teaching proposals. Special Education. School inclusion. Academic field.